CHILD MORTALITY, NUTRITIONAL STATUS AND HEALTH CARE IN DOMPU DISTRICT, WEST NUSA TENGGARA, 2007–2011 - Primasari Primasari (Widyariset, 2013)
Child mortality in West Nusa Tenggara province at 103 per 1000 live births, while the infant mortality rate Dompu 82 per 1000 live births. Therefore, it is necessary to study the explanation of the index child mortality in Dompu district, as well as view the status of nutrition and health care. This research is a descriptive study, the secondary data collection of health profiles Dompu DHO has been published within the period of 5 years from 2007 to 2011. Variabel taken are indicators related to child mortality. The results of this study indicate that the number of infant deaths rose sharply in 2009, by 39 per 1000 birth when compared to 2007 (1 per 1.000 births) and in 2008 (3 per 1000 births). In 2010, infant mortality fell to 12 per 1.000 births, but increased again in 2011 to 34 per 1000 births. Based on the findings in this study, it is necessary to improve the coverage of deliveries assisted by health personnel in order to reduce infant mortality. This can be done by exam the cause of child mortality.